The Impact of Shift Work on Nurses' Mental and Physical Health: A Review of Recent Literature - Hutapea, Kimberley Maharani Maulibulung; Hutapea, Dwight Mahaputera Marulitua (PT. Anagata Sembagi Education, 2025)
Irregular work shifts in the health care system can have a significant impact on the physical and mental health of nurses. This study uses a descriptive qualitative approach to explore the experience of nurses in facing the challenges of shift work. A total of 30 nurses with at least two years of experience in night and rotation shifts were selected as participants. Data were collected through semi-structured interviews, participatory observations, and document analysis. The results showed that changes in circadian rhythm due to shift work had an impact on sleep quality, increasing the risk of fatigue, cognitive impairment, and work errors. In addition, nurses with poor sleep patterns are more prone to metabolic problems such as obesity and diabetes, as well as psychological disorders such as stress and depression. High workloads and a lack of balance between work time and rest contribute to increased burnout rates, which ultimately decreases job satisfaction as well as the quality of health care. Nurses develop individual coping strategies, such as sleep pattern setting, relaxation techniques, and healthy eating, and rely on social support from colleagues and family. Adaptive institutional policies, such as more humane shift rotation and shift duration restrictions, are needed to maintain a balance between nurses' work and personal lives. With a more flexible and healthy work system, the welfare of health workers can be improved, so that the quality of service to patients remains optimal.